2015
DOI: 10.1088/0004-637x/800/2/129
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Umbral Flashes and Running Sunspot Waves With the Interface Region Imaging Spectrograph

Abstract: We present simultaneous, high-resolution, multi-temperature observations of running waves and umbral flashes in a sunspot with the Interface Region Imaging Spectrograph. We analyze intensity variations in slit-jaw images to investigate the relationship between running waves in the 1400 Å (Si iv/transition region) passband and umbral flashes in the 2796 Å (Mg ii/chromosphere) passband. Using global wavelet analysis, we find that the dominant wave periods increase from approximately 150 s near the sunspot center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…Tian et al (2014a) performed detailed analysis of the TR spectra and identified strong signals of shock waves in the TR above sunspots. IRIS observations of these shocks at different layers appear to be consistent with the scenario of upward propagating magnetoacoustic shock waves along inclined magnetic field lines (Madsen et al 2015).…”
Section: Dynamics In the Tr Above Sunspotssupporting
confidence: 78%
“…Tian et al (2014a) performed detailed analysis of the TR spectra and identified strong signals of shock waves in the TR above sunspots. IRIS observations of these shocks at different layers appear to be consistent with the scenario of upward propagating magnetoacoustic shock waves along inclined magnetic field lines (Madsen et al 2015).…”
Section: Dynamics In the Tr Above Sunspotssupporting
confidence: 78%
“…Although the change in magnetic field inclination angles across the umbra has been shown to produce similar effects (Reznikova et al 2012;Madsen et al 2015), the restriction of this behavior in our current observations to chromospheric channels (i.e., excluding the transition region observations) is puzzling and demands further exploration.…”
Section: Discussionmentioning
confidence: 72%
“…Vice versa, the larger apparent velocities of around 30-70 km s −1 at photospheric layers fit well into the trend of decreasing horizontal velocities at the inner penumbra toward higher layers. The topological model of the sunspot's magnetic field (e.g., Westendorp Plaza et al 1997), the field-guided propagation of running penumbral waves, and their visual appearance at a certain layer can explain this behavior (Bloomfield et al 2007;Madsen et al 2015). In the penumbra, the magnetic field inclination increases radially from the vertical umbral field.…”
Section: Resultsmentioning
confidence: 99%